The evaluation of congenital double elevator palsy with magnetic resonance imaging - (:unkn) unknown (My University, 1999)
Orbital and cranial magnetic resonance imaging (MRI) was performed in nine patients with congenital double elevator palsy. On orbital MRI examination, superior rectus (SR) and inferior rectus (IR) muscles were specifically evaluated with sagittal and coronal views. Bell's phenomenon was present in three cases and four patients had positive forced duction tests. The vertical recti did not show any difference in either size or signal intensity when compared to controls. There was no denervation atrophy in the SR muscle. On cranial MRI examination, we were unable to demonstrate any abnormal signal intensity. The results of this study suggest that a paretic SR muscle is unlikely to be responsible for the clinical picture in congenital double elevator palsy, since a paretic SR muscle causing such a severe limitation of upgaze would be expected to have denervation atrophy.
Keywords: Double elevator palsy; Magnetic resonance imaging; Superior rectus palsy